The Phenomenon of Herding Behavior in Impulse Buying Against the Labubu Doll Trend: Analysis of Tabdzir Verse in the Tafsir Kementerian Agama RI - Abdillah, Abdillah Nurul Bahri; Muhamad Takrip; Dede Rodin; Muhammad Saifullah (Jurnal Semiotika-Q, 2025)
This research aims to explore the phenomenon of herding behavior and impulse buying in the consumption trend of Labubu Dolls, and relate it to Islamic teachings on tabdzir or waste. This research uses a qualitative method based on literature study, with primary data sources from the Qur'anic verses that discuss consumptive behavior and focus on the interpretation of the Tafsir Kementerian Agama RI. The results show that impulsive behavior in buying Labubu Dolls is influenced by social media, popular trends, and emotional impulses, reflecting a consumptive lifestyle that  is prohibited  in  Islam. The concept of tabdzir provides a perspective on the importance of wise wealth management and moderation in shopping. This research contributes to enriching the understanding of healthy consumption within the framework of Islamic teachings and can be applied in everyday life, especially in relation to the widespread use of social media. This research aims to explore the phenomenon of herding behavior and impulse buying in the consumption trend of Labubu Dolls, and relate it to Islamic teachings on tabdzir or waste. This research uses a qualitative method based on literature study, with primary data sources from the Qur'anic verses that discuss consumptive behavior and focus on the interpretation of the Tafsir Kementerian Agama RI. The results show that impulsive behavior in buying Labubu Dolls is influenced by social media, popular trends, and emotional impulses, reflecting a consumptive lifestyle that  is prohibited  in  Islam. The concept of tabdzir provides a perspective on the importance of wise wealth management and moderation in shopping. This research contributes to enriching the understanding of healthy consumption within the framework of Islamic teachings and can be applied in everyday life, especially in relation to the widespread use of social media.